Desain Pembelajaran Humanistik di SMAN 19 Gowa: Ketika Estetika dan Teknologi Bersatu dalam Pendidikan - Arsyad, Ernawati; Damayanti, Resty Rahayu; Suhaeb, Firdaus W. (Universitas Syiah Kuala, 2025)
This study analyzes the implementation of a humanistic learning design at SMAN 19 Gowa, realized through the integration of aesthetics and technology. This phenomenon is examined due to the pressing need to align humanistic values with digital innovation in education. Utilizing a qualitative approach with a humanistic interpretive paradigm, the research involved in-depth interviews and observations to understand the lived experiences of teachers and students in constructing meaningful and human-centered learning processes. Data were analyzed using thematic analysis techniques. The findings indicate that this design creates an existential space where teachers act as empathic facilitators and technology functions as a medium for humanization. The integration of aesthetics (as a bridge between logic and empathy) and technology (as an extension of creative expression) significantly boosts students intrinsic motivation, emotional engagement, and moral awareness. The study concludes by proposing the Humanistic Aesthetic Technopedagogy model as a conceptual framework to ensure education remains a process of human growth, creativity, and ethical awareness in the digital era.